Autobiographical memory in adult offspring of traumatized parents with and without posttraumatic stress symptoms. (30th August 2016) - Wittekind, Charlotte E.; Jelinek, Lena; Moritz, Steffen; Muhtz, Christoph; Berna, Fabrice
Abstract: The present study examined potential transgenerational effects of trauma on autobiographical memory in adult offspring of elderly participants with and without PTSD symptoms who were exposed to an early trauma during childhood. As traumatization is associated with reduced memory specificity for past events, we hypothesized that offspring of traumatized parents might be exposed to a less elaborative narrative style, which, in turn, might result in less specific autobiographical memories in the offspring. Results show that autobiographical memory specificity did not differ significantly between adult offspring of traumatized elderly participants with PTSD symptoms, without PTSD symptoms, and non-traumatized elderly participants. Highlights: First study assessing transgenerational effect of trauma on autobiographical memory. Children of traumatized individuals were compared to children of healthy controls. Autobiographical memory specificity did not differ significantly between groups.